Dinamika profesi Pendidik: Profil Guru Profesional dalam Menghadapi Tantangan di Era Digital Tingkat SMP di SMP Negeri 35 MEDAN - Adelina M. Aritonang; Eka Putriani Sihombing; Ertika S. Pasaribu; Herlide Purba; Iwain O. Nababan; Pebryna R. Siburian; Jamaludin Jamaludin (LPPM Politeknik Pratama, 2024)
This research aims to analyze the profile of professional teachers at SMP Negeri 35 Medan in facing challenges in the digital era. The research method used is descriptive qualitative with data collection techniques through interviews and observation. The research results show that professional teachers in junior high schools have utilized digital technology in the learning process. They face various challenges such as technology integration in synchronization and selection of relevant content. These findings provide insight into teachers' efforts to improve their digital competencies to provide effective learning in the digital era.